Experimental Investigation on the Effect Polypropylene Fibre and E-Waste Fibre Embedded in Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
The main building material that can’t be  ignored even it’s weak in tension and lead to various  environmental problems during it’s production is concrete.  Properties of concrete can be enhanced using fibre in  concrete. Using fibre from waste of plastic in concrete to  some percentage increases strength as well as durability of  concrete and solve disposal problems of plastic waste in  environment. From electronic waste Polyvinyl chloride  cables (PVC) are used as fibre and from polypropylene (PP)  packing bag of cement are used as fibre in concrete. Both  are used in 0%, 0.25%, 0.50%, 0.75% and 1% by weight of  cement in concrete. Fresh and harden properties for both  concrete with polypropylene fibre and with electronic waste  fibre is determined and hybrid of optimum values  calculated is used in a single mix and compressive strength  is calculated. Results show that 0.75% and 0.50% is  optimum value of concrete with electronic waste fibre and  concrete with polypropylene fibre with 49% and 17.5%  increase in concrete strength compared to normal concrete  respectively and can be used in a single mixture. Concrete  with hybrid of polypropylene fibre and electronic waste  fibre shows enhancement of 56% in compressive strength.  The hybrid of PPFRC and EFRC polypropylene fibre keep  cracks small and e-waste fibre shows enhancement in  mechanical properties.
Keywords: Concrete; Cement Bag; Polyvinyl Chloride Fibre; Compressive Strength; Hybrid Fibre Reinforced Concrete